Growing the Rural Nonfarm Economy to Alleviate Poverty : An Evaluation of the Contribution of the World Bank Group - Independent Evaluation Group (World Bank, Washington, DC, 2017)
Most of the world’s poor live in rural areas and rural non-farm activities are an important part of their livelihoods strategies. However, for the poor to benefit from the rural non-farm economy (RNFE), they need to overcome a host of human, physical, financial, institutional and social capital constraints. The World Bank Group has highlighted the RNFE in its strategies. From 2004 to 2014, the BankGroup implemented 1,141 projects, valued at $46.5 billion that included support for RNFE activities. However, the Bank Group currently lacks an articulated approach to developing the RNFE to alleviate poverty. Many units have products in this space, but there is no coordinating mechanism. There is a gap between poverty and growth-oriented approaches in the RNFE. Those designed toreach the rural poor have reduced vulnerability and increased access to services but have notgenerated sufficient, sustained income to lift the rural poor out of poverty. Those RNFE projects with a growth aim—mainly value chain approaches—achieved increased revenues but mostly withoutevidence of benefits for the poor. Spillover effects are not measured. Efforts to bridge this gap asked approaches adept at service delivery to achieve earned income goals beyond their original design. Where IFC’s investments in food processing have had strong links to rural areas, they have generally generated positive rural employment outcomes and demonstrated links to the RNFE. However in its agribusiness portfolio, there was little in project design that targeted or tracked benefits for the poor.IFC’s retail investments linked to rural areas seek to increase the availability of goods and drive down costs for rural consumers. However, none of the investments tracked consumer benefits (costs) and only a few included local sourcing. In spite of examples of where market power has adversely affected poor value chain participants, the risks imposed by market structure, its impact on the poor, and related mitigants are rarely treated explicitly in project documentation. The Bank has been a leader in researching the RNFE, including its link to poverty. But there is a gapon the diagnostic and analytics side that has been addressed occasionally but not systematically. Addressing binding constraints is key to linking the rural poor to productive activities in the RNFE. Bank–financed rural transport projects have not measured their contribution to local economic gains,in spite of intentions to achieve this. Rural connectivity is being achieved through synergies between transport and agriculture lending but mainly in transitioning economies. Basic literacy and skills are critical enablers in the RNFE, but dialogue is lacking between the Agriculture and Education GPs. Although many value chain projects include a skills component, impact is not assessed. The delivery of sustainable, low-cost rural financial services requires research, piloting, and scaling up of innovative business models to reach the underserved. World Bank support has extended some financial services to the poorest rural segments, but subsidization raises questions about sustainability, crowding out, and potential for politicization. IFC investments reach countries with high exclusion rates, but only a fraction caters to the lower end of the retail segment.